CULTIVATING ENTREPRENEURIAL VALUES TO IMPROVE SEVERAL ASPECTS OF EARLY CHILDHOOD DEVELOPMENT: THE CASE STUDY IN KHALIFAH KINDERGARTEN YOGYAKARTA - Nurkamelia Mukhtar AH; Abdul Munip (Sunan Kalijaga International Journal on Islamic Educational Research, 2018)
The entrepreneurial values such as independent, creativity, risk-taking ability, and responsibility play an important role in directing early childhood development, especially in the aspect of social-emotional, language, and cognitive. Khalifah kindergarten which is based on entrepreneurship, support the life skills development of children with several of excellent programs for example Market Day. This study is intended to know the reason of Khalifah Kindergarten in applying entrepreneurship program, the process and impact of the program on the aspects of early childhood development. The findings of this study are: first, Khalifah Kindergarten wants to achieve its mission in integrating entrepreneurial values in all aspects of early childhood development by introducing them to become Muslims entrepreneur. Second, the process of increasing the entrepreneurial values is implemented through Beyond Centre and Circle Time (BCCT) learning system, entrepreneurship activities such as market day, cooking classes, field trips, angklung music as an extracurricular activity, and habituation through continuous interviews with the students. Third, the impact of entrepreneurial values can be proved in several aspects of development. In the social-emotional aspect, the children have empathy for others. In the cognitive aspect, the children have creative thinking. In an aspect of linguistic development, they become communicative, and in the physical-motor aspect, the children have the high spirit to produce a work.